2017
DOI: 10.1016/j.addbeh.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment and age of alcohol and marijuana initiation in high-risk youth

Abstract: Externalizing behavior is one pathway from childhood maltreatment to age of substance use initiation. Services for maltreated youth should incorporate substance use prevention, particularly among those with early externalizing problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
3
33
0
3
Order By: Relevance
“…Among the main hypotheses raised for this association is the concept of cumulative risk effect that includes a wide range of factors such as the type of abuse, time of exposure to abuse, severity of the traumatic event and age at onset of drug use. Previous studies have demonstrated that greater severity and chronicity of CM are associated with a more severe SUD and early age of alcohol, opioid and marijuana initiation (Proctor et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the main hypotheses raised for this association is the concept of cumulative risk effect that includes a wide range of factors such as the type of abuse, time of exposure to abuse, severity of the traumatic event and age at onset of drug use. Previous studies have demonstrated that greater severity and chronicity of CM are associated with a more severe SUD and early age of alcohol, opioid and marijuana initiation (Proctor et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Child maltreatment is the abuse (acts of commission, including physical, emotional, and sexual abuse) and neglect (acts of omission, including failure to provide necessary care that meets a child's basic needs, such as food, household cleanliness, and supervision) of children under 18 years of age (Leeb, Paulozzi, Melanson, Simon, & Arias, ). Numerous studies have shown associations between child abuse and neglect and adolescent substance use, including substance abuse that begins at an earlier age and more severe substance use (Gabrielli, Jackson, & Brown, ; Proctor et al., ; Tonmyr, Thornton, Draca, & Wekerle, ). Evidence suggests that substance use occurring in late childhood or early adolescence early substance use may be a mechanism linking childhood maltreatment and later‐adolescent substance use (Lansford, Dodge, Pettit, & Bates, ).…”
mentioning
confidence: 99%
“…Evidence suggests that substance use occurring in late childhood or early adolescence early substance use may be a mechanism linking childhood maltreatment and later‐adolescent substance use (Lansford, Dodge, Pettit, & Bates, ). Maltreated youths initiate substance use at earlier ages (Proctor et al., ). Additionally, adolescents who initiate substance use earlier are more likely to engage in subsequent substance use, including the development of substance use disorder (Tucker, Ellickson, Orlando, Martino, & Klein, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, physical abuse was most strongly associated with adolescent nicotine (odds ratio [OR]: 1.8–6.1), alcohol (OR: 0.8–8.9), and drug use (OR: 1.8–20.4) compared with other types of child maltreatment (i.e., sexual abuse, emotional abuse, and neglect). Consistent with the review, physical abuse has repeatedly been found to be associated with higher levels of adolescent substance use in studies that utilized national datasets, such as the National Longitudinal Study of Adolescent Health (Snyder & Monroe, ), the National Survey of Child and Adolescent Well‐being (Snyder & Smith, ; Shin, Miller, & Teicher, ), and the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN; Proctor et al, ).…”
Section: Introductionmentioning
confidence: 60%